This Side of Heaven - Kingsbury, Karen (New York : Center Street, 2009)
"A story of family secrets, broken relationships, and a love strong enough to span a nation"--Provided by publisher.
Keywords: Fathers and daughters -- Fiction; Family secrets -- Fiction